2018
DOI: 10.3390/fermentation4010015
|View full text |Cite
|
Sign up to set email alerts
|

Adding Flavor to Beverages with Non-Conventional Yeasts

Abstract: Abstract:Fungi produce a variety of volatile organic compounds (VOCs) during their primary and secondary metabolism. In the beverage industry, these volatiles contribute to the the flavor and aroma profile of the final products. We evaluated the fermentation ability and aroma profiles of non-conventional yeasts that have been associated with various food sources. A total of 60 strains were analyzed with regard to their fermentation and flavor profile. Species belonging to the genera Candida, Pichia and Wickerh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
(16 reference statements)
0
41
0
7
Order By: Relevance
“…According to several existing studies, W. anomalus releases significant amounts of ethyl butyrate and ethyl acetate leading to fruity flavor impressions. P. kluyveri and Z. florentina produce considerable amounts of pleasant esters, such as isoamyl acetate, during the fermentation process of all-malt wort, which can be attributed to the fruity banana-like sensory perception [5,7,43,47]. While the W. anomalus (WA1 to WA4, WA25) strains investigated in this study revealed a broad range of different positive to negative sensory odor impressions, P. kluyveri (PK1) actually produced remarkable amounts of pleasant isoamyl acetate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to several existing studies, W. anomalus releases significant amounts of ethyl butyrate and ethyl acetate leading to fruity flavor impressions. P. kluyveri and Z. florentina produce considerable amounts of pleasant esters, such as isoamyl acetate, during the fermentation process of all-malt wort, which can be attributed to the fruity banana-like sensory perception [5,7,43,47]. While the W. anomalus (WA1 to WA4, WA25) strains investigated in this study revealed a broad range of different positive to negative sensory odor impressions, P. kluyveri (PK1) actually produced remarkable amounts of pleasant isoamyl acetate.…”
Section: Discussionmentioning
confidence: 99%
“…The applied yeasts were cultured in a medium based on glucose and the resulting volatile compounds were detected by gas chromatography/mass spectrometry (GC/MS) measurement. Only the promising species were additionally analyzed for their maltose utilization on serial-dilution plate assays [7].The study presented here includes screening the brewing ability of 110 non-Saccharomyces strains with optimized screening conditions as the metabolism of the full range of main wort carbohydrates (glucose, fructose, sucrose, maltose and maltotriose [8]) were taken into account. As maltose and maltotriose represent more than 80% of the total carbohydrates in brewer's wort [9], the ability to ferment these two substances is essential for a fast, complete and predictable fermentation [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The fermented mead, as well as the unfermented musts, were examined. The method was adapted from Ravasio et al [49]. Briefly, 2.5 mL of sample was placed in 20 mL glass vials with 0.75 g of NaCl and 10 µL of internal standard (2-octanol, 50 µg/mL).…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%